Foster Care from a Historical Perspective. (19th October 2015) - Briggs, Freda; Hunt, Susan
Abstract : Foster care has been available in Australia for almost 150 years. Carers have long been recognised as "the ultimate volunteers" who care for the most traumatised, emotionally disturbed children in the nation. Given that they provide the foundation stone of the child protection system, one might expect carers to be supported and valued. Numerous studies have shown otherwise. Warning signs over the years have been ignored by child welfare authorities resulting in carers leaving the service faster than they could be recruited and the most needy young children being placed in caravan parks, cheap motels and group homes supervised by occasional, inadequately trained, generalist carers employed on seven hour contracts by agencies.